Disturbance of osteonal bone remodeling and high tensile stresses on the lateral cortex in atypical femoral fracture after long-term treatment with Risedronate and Alfacalcidol for osteoporosis - Fumitaka Hirano (Bone Reports, 2021)
An 83 year-old Japanese woman complained of left lateral thigh pain following a low-energy fall 4 months prior to admission. She had been treated for osteoporosis with Risedronate and Alfacalcidol for the previous five years. She was diagnosed with an atypical femoral fracture (AFF) according to the American Society for Bone and Mineral Research (ASBMR) Task Force revised criteria. Radiographs revealed cortical thickening and a transverse radiolucent fracture line in the lateral cortex of the shaft. MRI showed a high intensity signal on the T2WI image 1 cm long in the lateral cortex. The patient had normal levels of bone resorption and formation biomarkers except for low 25(OH) Vitamin D. Double fluorescent labeling was done preoperatively.Due to significant bowing, a corrective osteotomy and intramedullary nailing were performed, and the resected bone wedge was analyzed by bone histomorphometry. Three ground sections of the lateral cortex at the fracture site showed many and large pores, with or without tetracycline labeling. Histomorphometric assessment was done on intracortical pores, classified by a novel criteria, only to assess size of the pores to know prolonged osteoclastic activity and its characteristics of inner surfaces to assess whether bone formation has been occurring or not in labeling period in remodeling cycle, and coalition of multi-pores. Increased size with widespread variation of pores suggested prolonged osteoclastic activity in the reversal/resorptive phase. Bone labeling showed lamellar bone on the endocortical surface.We hypothesize that the case had developed from a regional disturbance of osteonal remodeling in the lateral cortex, in which accumulated microcracks might have initiated a resorption process resulting in resorption cavities, i.e., pores, which became larger due to prolonged activity of secondary osteoclasts. Various sized pores could form lamellar bone, still forming at the time of biopsy, some had formed lamellar bone, but stopped to form before labeling and not to start to form at all, probably due to incomplete coupling. Endocortical lamellar bone might had started to resorbed to smooth off endocortical surface, followed by formation of lamellar bone. The endocortical bone formation was assessed and its formation period is about 2.7 years.A finite element analysis using preoperative CT data revealed high tensile stresses on the lateral aspect of the femur. Histomorphometric results suggest that there might be more pores in the tensile area than the compressive area. These findings may subsequently connect accumulation of microcracks, an increase of size and number of pores and coalition and subsequent fracture in the lateral cortex.